Internet of things: investigating its social and legal implications in a connected society - Zulhuda, Sonny; Mohamed, Sidi Mohamed Ould (Universitas Muhammadiyah Yogyakarta, 2017)
The myriad of successive technological waves have affected social lives and challenged legal norms in modern societies. The Internet of Things (‘IoT’) is one of those technological waves and is considered by many as the first real evolution of the Internet. It is about the digitization of physical things and objects, which enable them to communicate information about themselves and their surrounding environment with each other. Connected environment such as this could undeniably impact various aspects of life be it trade, services, healthcare, education as well as public governance. The “Internet of Things” also challenge existing legal concepts and this has in turn led to questions about the effectiveness and ability of laws to coexist with the rapid technology. This paper attempts to investigate the social and legal implications of the Internet of Things and its impacts on both society and governance, including on issues of data privacy, data security and data ownership. It is an introductory, descriptive and hypothetical analysis. It is also a preview to many more legally substantive questions surrounding the deployment of IoT in both commercial and non-commercial activities. This study is timely as it precedes the ongoing discussions about IoT from legal and social perspectives.